2007
DOI: 10.1136/bjo.2006.106278
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of change in visual function in patients treated with pegylated interferon alpha for hepatitis C in the UK

Abstract: In contrast to previous studies in America and south-east Asia, our findings based on a UK cohort suggest that routine ophthalmic screening is not essential for patients with hepatitis C treated with pegylated interferon alpha who have no subjective visual complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 14 publications
0
16
2
1
Order By: Relevance
“…In a study of 25 CHC patients, there was a 16% prevalence of retinopathy on a 3-month eye exam; however, pre-treatment eye exams were not performed [14]. In another recent study that enrolled 40 patients with baseline eye exams, only ten patients showed up for follow-up at 6-9 months limiting conclusion on outcome [15]. Our study is the first to have baseline exams, follow-up exams on therapy and posttherapy exams.…”
Section: Discussionmentioning
confidence: 74%
“…In a study of 25 CHC patients, there was a 16% prevalence of retinopathy on a 3-month eye exam; however, pre-treatment eye exams were not performed [14]. In another recent study that enrolled 40 patients with baseline eye exams, only ten patients showed up for follow-up at 6-9 months limiting conclusion on outcome [15]. Our study is the first to have baseline exams, follow-up exams on therapy and posttherapy exams.…”
Section: Discussionmentioning
confidence: 74%
“…PEG-IFN-associated retinopathy has been observed to have similar clinical features and a reported incidence of 16–29.3%, which is somewhat lower than that of IFN-associated retinopathy [17,18,19,20]. In this study, the incidence of retinopathy was identified as 21.73%.…”
Section: Discussionmentioning
confidence: 70%
“…Studies by Jain et al (19), Cuthbertson et al (13) and Okuse et al (20) have shown a relatively higher incidence of retinopathy (symptomatic or asymptomatic) ranging from 19% to 64% during treatment with IFN; however Malik et al (21) and Panetta et al (22) showed relatively lower incidence of retinopathy (0% and 3.8%, respectively). Also, the estimated prevalence of diabetic retinopathy and vision-threatening diabetic retinopathy in USA was 28.5% and 4.4% respectively, among persons with diabetes aged 40 years and older.…”
Section: Discussionmentioning
confidence: 97%